2020
DOI: 10.3390/brainsci10040252
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Intracerebral Hemorrhage Descriptors with Clinical Factors

Abstract: The association between intracerebral hemorrhage (ICH) shape and a poor treatment outcome has been established by few authors. We decided to analyze whether computationally assessed hemorrhage shape irregularity is associated with any known predictors of its poor treatment outcome. We retrospectively analyzed 48 patients with spontaneous intracerebral hemorrhage. For each patient we calculated Fractal Dimension, Compactness, Fourier Factor and Circle Factor. Our study showed that patients above 65 years old ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As important factors in HE and prognosis, the shape features of the initial hematoma have been described by various methods and demonstrated to be associated with outcomes. These studies have included qualitative analytical variables, such as Barras grade, island sign and satellite sign ( 8 , 14 , 20 ), and quantitative analytical variables, such as the SR index, compactness, Fourier factor and fractal dimension ( 15 , 21 , 35 ). The present study is the first to relate changes in hematoma morphology to the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As important factors in HE and prognosis, the shape features of the initial hematoma have been described by various methods and demonstrated to be associated with outcomes. These studies have included qualitative analytical variables, such as Barras grade, island sign and satellite sign ( 8 , 14 , 20 ), and quantitative analytical variables, such as the SR index, compactness, Fourier factor and fractal dimension ( 15 , 21 , 35 ). The present study is the first to relate changes in hematoma morphology to the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the patterns of morphological change have not been explored. Additionally, many studies have found that the initial shape of a hematoma was associated with the quality of outcomes ( 14 , 15 ). However, few studies have focused on the relationship between morphological changes and patient prognosis.…”
Section: Introductionmentioning
confidence: 99%